1984
DOI: 10.1258/002367784780958295
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pineal body tumours (pinealomas) in Wistar rats; a histological and ultrastructural study

Abstract: SummaryThe pathology of 5 cases of pinealomas in Wistar rats used in long-term toxicological studies is described both grossly, microscopically and ultrastructurally, together with a review of the related literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
3
8
1
1
Order By: Relevance
“…Lymphoma and leukemia accounted for 6% of neoplasms, slightly less than the incidence of 11% noted in our first review and much less than the high frequency of large granular cell leukemia in F344 rats (Solleveld et al, 1984). Neoplasms of nervous system are uncommon in Wistar rats (Dagle et al, 1979;Sumi et al, 1976;Al Zubaidy and Malinowski, 1984;Maekawa et al, 1984) and in this review accounted for 2.1% of tumors in 2.3% of all rats. Unlike our previous review in which astrocytomas were the most common neural neoplasm, granular cell meningiomas were the most common neoplasm in this review.…”
Section: Discussionsupporting
confidence: 46%
“…Lymphoma and leukemia accounted for 6% of neoplasms, slightly less than the incidence of 11% noted in our first review and much less than the high frequency of large granular cell leukemia in F344 rats (Solleveld et al, 1984). Neoplasms of nervous system are uncommon in Wistar rats (Dagle et al, 1979;Sumi et al, 1976;Al Zubaidy and Malinowski, 1984;Maekawa et al, 1984) and in this review accounted for 2.1% of tumors in 2.3% of all rats. Unlike our previous review in which astrocytomas were the most common neural neoplasm, granular cell meningiomas were the most common neoplasm in this review.…”
Section: Discussionsupporting
confidence: 46%
“…Based on present findings, this tumor was diagnosed as benign. The formation of a rosette or a pseudo-rosette pattern and smooth muscle fibers in the such stroma have also described in the pineal gland tumors in rats [1,6,9,12], but there were no findings in the present case.…”
supporting
confidence: 41%
“…The malignant pineal gland tumor is characterized by cellular pleomorphism, high mitotic activity, necrosis, and, most important, invasive growth into adjacent tissue [1,8,12]. However, it has been reported that high mitotic activity is common in benign pineal gland tumors in rats [3,[9][10][11]13].…”
mentioning
confidence: 99%
“…( Al Zubaidy and Malinowski 1984 ; Botts et al 1994 ; Capen et al 2001 ; Coca et al 1992 ; Fraser 1986 ; Furukawa et al 1999 ; Götz et al 1992 ; Heath and Winokur 1998 ; Hirato and Nakazato 2001 ; Jouvet et al 2006 ; Koestner and Solleveld 1996 ; Korf et al 1990 ; Krinke et al 1985 ; Krinke et al 2000 ; Maekawa et al 1984 ; Rubinstein 1972 ; Schachner et al 1984 ; Treumann et al 2015 ; Vogel and Fuller 2003 ; Walker et al 1994 ; Yamamoto et al 1991 )…”
Section: Pineal Glandunclassified